2021
DOI: 10.1186/s12889-021-10549-7
|View full text |Cite
|
Sign up to set email alerts
|

NO2 exposure increases eczema outpatient visits in Guangzhou, China: an indication for hospital management

Abstract: Background Ambient nitrogen dioxide (NO2) is a common air pollutant in developing countries and causes skin conditions, but its effect on eczema in subtropical areas is not clear in China. Object To measure the effect of short-term exposure of NO2 on the incidence of eczema and the change of outpatient visits. Methods Data of daily temperature, air pollutants, and outpatient visits from 2013 to 2018 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To date, no more research has revealed the effects of different combinations of pollutants on eczema. The effects of single pollutants on eczema still have different results in different regions, such as previous studies have revealed that O 3 and NO 2 were not associated with increased patient visits for AD but our team has revealed that NO 2 exposure increases eczema outpatient (10,27). The effect of pollutants on eczema is still inconclusive, thus, the effect of combined pollutants has not been concluded.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…To date, no more research has revealed the effects of different combinations of pollutants on eczema. The effects of single pollutants on eczema still have different results in different regions, such as previous studies have revealed that O 3 and NO 2 were not associated with increased patient visits for AD but our team has revealed that NO 2 exposure increases eczema outpatient (10,27). The effect of pollutants on eczema is still inconclusive, thus, the effect of combined pollutants has not been concluded.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, SO 2 can enhance the production of active oxygen and further reduce the content of antioxidants in the skin (62). Moreover, our previous study revealed that outpatient visits for patients with eczema were positively associated with short-term exposure to ambient NO 2 (10). NO 2 will damage the skin integrity which conducts a higher risk of exposure to allergic substances (63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all studies (17/18) were determined to have low risk for bias (Table 2). We used the five GRADE domains (study limitations, consistency of effect, precision, directness and publication bias) 49 to evaluate the overall body of evidence on the association between air pollution and healthcare use for AD and determined a moderate grade of certainty (Appendix S1). This was primarily due to consistent results across studies for most air pollutants, precision of the results of analyses conducted with large sample sizes, and the directness of measuring physician‐diagnosed AD with health services data.…”
Section: Resultsmentioning
confidence: 99%
“…Being the largest organ of the human body, the skin can be exposed to air pollutants from the external environment under different weather conditions. When the amount of air pollution exposure exceeds the resilience threshold for self protection, it may result in skin diseases (Szyszkowicz et al, 2010;Xu et al, 2011;Li et al, 2016;Liu et al, 2018;Ren et al, 2019;Chao et al, 2021;Zhang et al, 2021). Thus, the effects of NO2 exposure on skin diseases have received increasing attention.…”
Section: Introductionmentioning
confidence: 99%